IMPLEMENTATION OF MANAGEMENT STRATEGY IN DEVELOPING THE QUALITY OF ISLAMIC EDUCATION AT PONDOK DARUL ARQAM ISLAMIC BOARDING SCHOOL MUHAMMADIYAH GOMBARA MAKASSAR CITY - Farida farida (JICSA : Journal of Islamic Civilization in Southeast Asian, 2023)
Abstract: Farida , 2023. Implementation of strategic management in developing the quality of Islamic education at the Darul Arqam Muhammadiyah Gombara Islamic Boarding School, Makassar City. Strategic management has an important role in improving the quality of education, for this reason this study aims to: 1) Analyze the effectiveness of strategic management implementation at the Darul Arqam Muhammadiyah Gombara Islamic Boarding School